2017
DOI: 10.3389/fneur.2017.00126
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Repetitive Transcranial Magnetic Stimulation Treatment in Chronic Tinnitus?

Abstract: BackgroundPrefrontal and temporo-parietal repetitive transcranial magnetic stimulation (rTMS) in patients suffering from chronic tinnitus have shown significant but only moderate effectiveness with high interindividual variability in treatment response. This open-label pilot study was designed to examine the general feasibility of an individualized fronto-temporal rTMS protocol and to explore what criteria are needed for a more detailed evaluation in randomized clinical studies.MethodsDuring the first session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 68 publications
4
31
4
Order By: Relevance
“…Second, although we have found that tDCS-TMS has the potential to improve the neuromodulatory effect, thereby creating an improvement of tinnitus, the results are limited as we have utilized only 200 pulses of low-frequency TMS due to time and space constraints in our hospital. Most of the previous tinnitus studies utilizing low-frequency TMS used 2,000 stimuli (46)(47)(48). In this regard, future tDCS-TMS studies using conventional TMS with 2,000 stimuli should be performed to explore further additive neuromodulatory effects on tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although we have found that tDCS-TMS has the potential to improve the neuromodulatory effect, thereby creating an improvement of tinnitus, the results are limited as we have utilized only 200 pulses of low-frequency TMS due to time and space constraints in our hospital. Most of the previous tinnitus studies utilizing low-frequency TMS used 2,000 stimuli (46)(47)(48). In this regard, future tDCS-TMS studies using conventional TMS with 2,000 stimuli should be performed to explore further additive neuromodulatory effects on tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the combination of two techniques—such as rPMS plus rTMS—is challenging to explore, as the complexity is increased by additional aspects such as the temporal relationship between peripheral and central stimulation. Consequently, future studies should try to concentrate on subgroup-specific effects of different treatment strategies or, more generally, on individualized treatment programs considering the very specific combination of possible causes and/or tinnitus-related alterations of a particular patient (Kreuzer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kreuzer et al's study suggested that individualized rTMS sessions' outcomes were better, since tinnitus is a personal symptom and hard to generalize [131]. In Yilmaz et al's study, THI score decreased by 8 points after the application of low-frequency rTMS, and also a statistically significant decrease was observed in tinnitus loudness and subjective score after the application of rTMS [50].…”
Section: Tms In the Treatment Of Tinnitusmentioning
confidence: 97%